Etik och moral inom ridsporten : med fokus på fälttävlan - Göransdotter, Elin (SLU/Dept. of Animal Environment and Health (until 231231), 2011)
Eventing is often called as the formula 1 in equestrian sports and comprises three disciplines: dressage, show jumping and cross-country. The sport provides excitement, challenge and joy and is the ultimate sport for intelligent riders and horses. Many are fascinated by the challenges the sport offers while other consider it foolhardy to ride a cross-country. Eventing is not a risk-free sport and has even been given the label of being one of the world´s most dangerous sports. What do those risks mean to the horse? And particularly, is it associated with good animal ethics to use the horse for eventing? Finding answers to these questions is not easy as it probably is not a clear and simple answer. The purpose of this work is then to highlight the ethical issues of eventing and highlight the ethical arguments for and against the use of horses for eventing.